ADAPTING HR DIGITALIZATION STRATEGIES IN TANAH LAUT’S MSMES AMID THE FOURTH INDUSTRIAL REVOLUTION - Khalid Al Hadring Smith; Annisa Sari; Nur Fadillah Suprayitno; Kurniawan Harminsyah Baharuddin (Jurnal Media Akademik (JMA), 2025)
This study aims to examine the adaptation strategies of human resource (HR) digitalization in micro, small, and medium enterprises (MSMEs) in Tanah Laut Regency in response to the challenges of the Industrial Revolution 4.0. The research method employed is a literature review from various relevant scholarly sources that capture the real conditions of MSMEs in Tanah Laut. The findings indicate that the main challenges faced by MSME actors include low digital literacy, limited technological infrastructure, and resistance to change. Nevertheless, digital adaptation has begun through HR training, utilization of digital platforms, and support from local government policies. This analysis is reinforced by the application of technology adaptation theories such as the Technology Acceptance Model (TAM), Diffusion of Innovations (DOI), and the Unified Theory of Acceptance and Use of Technology (UTAUT). The study highlights the critical importance of synergy between human resource capacity building, digital infrastructure development, and adaptive regulations in promoting sustainable digital transformation in the MSME sector.